Recombinant BCG: Innovations on an Old Vaccine. Scope of BCG Strains and Strategies to Improve Long-Lasting Memory - da Costa, Adeliane C.; Nogueira, Sarah V.; Kipnis, André; Junqueira-Kipnis, Ana Paula (Frontiers in Immunology, 2014)
BCG (Bacille Calmette-Guérin), an attenuated vaccine derived from Mycobacterium bovis, is the current vaccine of choice against tuberculosis (TB). Despite its protection against active TB in children, BCG has failed to protect adults against TB infection and active disease development, especially in developing countries where the disease is endemic. Currently, there is a significant effort towards the development of a new TB vaccine. This review article aims to address publications on recombinant BCG (rBCG) published in the last 5 years, to highlight the strategies used to develop rBCG, with a focus on the criteria used to improve immunological memory and protection compared with BCG. The literature review was done in April 2013, using the key words tuberculosis, rBCG vaccine and memory. This review discusses the BCG strains and strategies currently used for the modification of BCG, including: overexpression of M. tuberculosis (Mtb) immunodominant antigens already present in BCG; gene insertion of immunodominant antigens from Mtb absent in the BCG vaccine; combination of introduction and over expression of genes that are lost during the attenuation process of BCG; BCG modifications for the induction of CD8+ T cell immune responses and cytokines expressing rBCG. Among the vaccines discussed, VPM1002, also called rBCGΔureC::hly, is currently in human clinical trials. Much progress has been made in the effort to improve BCG, with some promising candidates, but considerable work is still required to address functional long-lasting memory.